Exploring L1 Transfer in German Learners of English: High Front Vowels, High Back Vowels and the BED/BAD Distinction - Kautzsch, Alexander (Research in Language, 2010)
Since the vowel systems of German and English are similar to some extent, German learners of English can be expected to transfer a considerable part of their German vowels to their L2 English. This paper traces the extent and source of positive and negative L1 transfer in two groups of university students from different German L1 backgrounds. To this end, acoustical analyses of three areas of vowel space are provided: high front vowels, high back vowels and mid/low front vowels. While positive transfer widely persists with high front vowels, learners refrain from consistently transferring high back vowels, probably owing to variability both in L1 German and in L2 English. In the case of mid/low front vowels negative transfer is reduced due to exposure to native English, and even more so due to formal instruction, which appears to accelerate the acquisition process